BASIC PRINCIPLES OF INDUSTRIAL PRACTICE OF CLINICAL PHARMACY - Sapatyi, A.L. (World of Medicine and Biology, 2013)
The article presents the main directions of the teaching of students of pharmacy faculty by the chair of clinical pharmacology and pharmacotherapy during the industrial practice in clinical pharmacy. The main purpose of the industrial practices of clinical pharmacy is to consolidate the theoretical knowledge of students and gaining of practical orientation and their use in future careers. To achieve this goal, the chair directed practical work of students in the departments of different profiles of clinical cardiology clinic and central city hospital. During the practical training, each student uses all provided in a hospital features that are the basis for future professional growth of pharmacist. The amount of knowledge that gets students during practical training, allows him to pursue in the future optimal pharmaceutical care, identify early clinical signs of disease and to approach negative influence of drugs.